Efek ekstrak etanol daun mimba (Azadirachta indica) terhadap kadar serum glutamat piruvate transminase (sgpt) dan gambaran histopatologi hepar pada mencit (Mus musculus) model hepatotoksik - Norbaldus J. Hayong; Meity M. Laut; Putri Pandarangga (Jurnal Veteriner Nusantara, 2019)
Azadirachta indica (neem), a plant used as traditional remedies, has been reported as hepatoprotector agent against liver damage of drugs abused. The present study aimed to investigate hepatoprotective activity ofethanolic extract of neem leaves on serum levels of glutamate pyruvate transaminase (SGPT) and histopathological studies of liver in rat’s model of aspirin-induced hepatotoxicity. Two to three months old male rats weighing between 20-30 g were used in this study. These rats were divided into 5 groups with three animals in each group. The experimental design were as follows: K1 is a negative control group and was treated with standard diet; K2 is a positive control group and was administered aspirin toxic dose (0.52 mg/30 g B.W., PO); P1 was treated with ethanolic extract of neem leaves (EEDM) dose I (0,7 mg/30 g B.W., PO) and aspirin toxic dose (0.52 mg/30 g B.W., PO); P2 was treated EEDM dose II (0,9 mg/30 g B.W., PO) and aspirin toxic dose (0.52 mg/30 g B.W., PO); and P3 was also treated with EEDM dose III (1.35 mg/30 g B.W., PO) and aspirin toxic dose (0.52 mg/30 g B.W., PO). The EEDM were administered to rats for 14 days, while aspirin toxic dose were given for the last three days (day 12, 13, and 14) during experiment. The serum levels were measured before treatment and on the last day (day 14). The results showed that the measurement of SGPT levels may not be a criterion, but the degree of liver damage can be seen in the histopathology. Histopathological observation of liver tissues of P1 and P2 shows minimal hepatocytes necrosis compare to other groups. In conclusion, EEDM dose I and II may have hepatoprotective activity against aspirin intoxication.